2005
DOI: 10.1007/s10585-006-9001-6
|View full text |Cite
|
Sign up to set email alerts
|

The expression of neurokinin-1 and preprotachykinin-1 in breast cancer cells depends on the relative degree of invasive and metastatic potential

Abstract: Breast cancer has a predilection for metastasis to the bone marrow. The preprotachykinin-I (PPT-I) gene has a central role in the early migration of breast cancer cells into the bone marrow, making this organ a latent repository of the cancer cells. This study investigated whether the invasive and metastatic potential of breast cancer cells correlate with the expression of the PPT-I gene and the receptors for its peptides, neurokinin-1 (NK-1) and NK-2. The studies compared cells that are non-tumorigenic (MCF12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Such knowledge could carry importance in a clinical setting, for example, to predict either prognosis and/or a treatment response with NK1R antagonists. Such a correlation has been described for the expression rate of the SP/NK1R complex and prognosis in other pediatric tumors (110,(152)(153)(154). For example, Garcia-Recio et al found that SP contributes to persistent transmodulation of the ErbB receptors, EGFR and HER2, in breast cancer, where it enhances malignancy and therapeutic resistance (110).…”
Section: The Nk1r As An Anti-tumor Target In Hepatoblastoma In the CLmentioning
confidence: 85%
“…Such knowledge could carry importance in a clinical setting, for example, to predict either prognosis and/or a treatment response with NK1R antagonists. Such a correlation has been described for the expression rate of the SP/NK1R complex and prognosis in other pediatric tumors (110,(152)(153)(154). For example, Garcia-Recio et al found that SP contributes to persistent transmodulation of the ErbB receptors, EGFR and HER2, in breast cancer, where it enhances malignancy and therapeutic resistance (110).…”
Section: The Nk1r As An Anti-tumor Target In Hepatoblastoma In the CLmentioning
confidence: 85%
“…It has previously been proposed that a correlation exists between the expression rate of the NK1R/SP complex and prognosis in various types of cancer (18)(19)(20)(21)(22). Garcia-Recio et al identified that SP contributes to persistent transmodulation of the ErbB receptors, epidermal growth factor receptor (EGFR) and human epidermal growth factor 2 (HER2), in breast cancer, acting to enhance malignancy and therapeutic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this signature discriminates invasive and metastatic from localized HB and predicts prognosis with high accuracy (16). Additionally, it has recently been suggested that the expression of TACR1 may correlate with a clinically worse prognosis in some cancers (18)(19)(20)(21)(22). However, scientific evidence for such an association remains scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The Tac1 gene produces several peptides belonging to the tachykinin family, of which substance P and neurokinin-A are its major products (9,10). In most peripheral cells, including breast epithelial cells, substance P and neurokinin-A interact with the seven-transmembrane, G protein -coupled receptors neurokinin-1 and neurokinin-2 (11,12). In nontransformed cells, neurokinin-1 and neurokinin-2 exhibit intracellular cross-talk so that each regulates the biological effects of the other (13).…”
Section: Introductionmentioning
confidence: 99%